2018
DOI: 10.1155/2018/4657396
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation by Methicillin-Resistant and Methicillin-SensitiveStaphylococcus aureusStrains from Hospitalized Patients in Poland

Abstract: Biofilm-mediated infections in the hospital environment have a significant negative impact on patient health. This study aimed to investigate biofilm production in vitro and the presence of icaABCD genes in methicillin-resistant S. aureus (MRSA) and methicillin-sensitive S. aureus (MSSA) strains isolated from hospitalized patients. MRSA (73) and MSSA (57) strains were evaluated for biofilm production by the microtiter plate method. The presence of ica operon was investigated by PCR. Out of 130 strains, 99.2% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
77
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 39 publications
11
77
1
4
Order By: Relevance
“…The presented data of the DNA microarray analysis revealed that all S. aureus isolates harbored icaACD genes regardless of their origin. These results were in agreement with several findings made in human infections [46], human nasal samples [47], sheep mastitis [48], and isolates from food matrices [6].…”
Section: Discussionsupporting
confidence: 93%
“…The presented data of the DNA microarray analysis revealed that all S. aureus isolates harbored icaACD genes regardless of their origin. These results were in agreement with several findings made in human infections [46], human nasal samples [47], sheep mastitis [48], and isolates from food matrices [6].…”
Section: Discussionsupporting
confidence: 93%
“…Community-acquired MRSA bacteremia has now surpassed hospital-acquired bacteremia worldwide, and it is frequently associated with other diseases, such as diabetes, ulcers, or chronic renal disease [12]. Despite the existence of an adequate treatment, MRSA is responsible for mortality rates of 20% to 40% in a period of 30 days [13]. Given the extreme severity of clinical complications from a generalized infection caused by S. aureus and its association with resistance to methicillin and most β-lactam antibiotics, it is extremely important to study the genetic characteristics of the most prevalent strains responsible for bacteremia in order to more effectively target the strategies for controlling these infections [14].…”
Section: Introductionmentioning
confidence: 99%
“…MRSA sample also showed biofilm results in 595 nm wavelength with detailed result as following: 37 percent strong biofilm, 49 percent moderate biofilm, and 13 percent weak biofilm from nasal swab, and catheter samples, and 13 percent weak biofilm in sample taken from nasal swab, and catheter of patients hospitalized in Poland. 18 MRSA strain is related to high mortality and morbidity rate related to the multi-drug resistance phenomenon and the ability of bacteria to produce a biofilm. 17,19 Bacteriaproducing biofilm can cause antibiotic resistance by the development of biofilm itself who initiated by a free moving bacteria called planktonic bacteria that attach to a surface and covered by a layer, such as proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The low level of biofilm production in MSSA which is marked by weak biofilm result at ODc reading associated with the low number of MSSA strains harboring icaAD genes compared to that of MRSA. 18 At Present, the standard methods available are used for AST in planktonic form and have a potential misinterpretation of the antimicrobial resistance in bacterial biofilm form. The minimal inhibitory concentration (MIC) and the minimal bactericidal concentration (MBC) of the conventional antibiotics to bacterial biofilm may increase up to 100-1000 times higher than planktonic form.…”
Section: Discussionmentioning
confidence: 99%